Recurrent Huge Left Bartholin’s Gland Abscess for One Year in a Teenager - Athanase Lilungulu; Bonaventura C. T. Mpondo; Abdallah Mlwati; Dismas Matovelo; Albert Kihunrwa; Balthazar Gumodoka (Case Reports in Infectious Diseases)
Bartholin’s gland abscess is the commonest worldwide reported abscess in gynaecological outpatient clinics; it has also been reported that Bartholin’s gland abscess is three times more common in occurrences compared to Bartholin’s gland cyst. It is more common in women who are at risk of acquiring sexually transmitted infections; however, other causes of infection should be investigated to exclude other causes of disease. We present the case of an 18-year-old female patient, a teenager of the reproductive age group, with the recurrent development of huge Bartholin’s gland abscess in a period of one year. The marsupialization surgical technique of repair was performed successfully. She was discharged home and she was scheduled to visit STI’s clinic where she was receiving regular screening for STI’s and she was also given health education regarding preventive measures for STI’s.